Good performance in difficult times? Threat and challenge as contributors to achievement emotions and academic performance during the COVID-19 outbreak - Malkoc, Smirna; Macher, Daniel; Hasenhütl, Sabine; Paechter, Manuela (Frontiers in Psychology, 2023)
The COVID-19 pandemic has emerged as one of the most formidable global crises, leading to the disruptions to education systems worldwide and impacting learning attitudes and psychological well-being of various learner groups, including university students. In this context, students’ appraisals of adverse learning situations play a key role. It is not just the learning situation, but rather students’ appraisal of it which impacts their emotions, attitudes, and behaviors in academic context. The aim of the present study was to investigate how university students’ challenge and threat appraisals were related to emotional learning experiences and learning outcomes during the COVID-19 pandemic. Furthermore, the study focuses on the role of personal and external resources for learning in this context. Altogether, 428 students, who attended a Psychology lecture at one Austrian university, filled in a questionnaire about their challenge and threat appraisals of learning circumstances during the COVID-19 pandemic, achievement emotions they experienced during this time as well as gender, proneness to anxiety, academic self-concept, and learning resources. Additionally, students’ performance in the examination was recorded. The structural equation model emphasizes a crucial role of challenge and threat appraisals for students’ achievement emotions in learning and exam preparation during the COVID-19 pandemic. Challenge appraisals were the strongest predictor for pleasant emotions and threat appraisals were strongest predictor for unpleasant emotions. Proneness to anxiety was related to threat appraisal as well as to experience of more unpleasant and, surprisingly, to positive emotions in adverse learning situation. Academic self-concept and learning resources were identified as important resources for learning in adverse learning situation. Unpleasant achievement emotions were directly and negatively related to academic performance and may thus be seen as a critical variable and crucial obstacle to academic performance. The present study provides implications for learning and instructions which could be implemented by universities in order to support learning and learning attitudes among university students in adverse learning situations.